2016
DOI: 10.1109/tdei.2015.005370
|View full text |Cite
|
Sign up to set email alerts
|

A review on critical evaluation of natural ester vis-a-vis mineral oil insulating liquid for use in transformers: Part 1

Abstract: In a long 130 years of its journey in service to mankind, the power transformer has grown in many aspects; ratings, performance, technology, aesthetics and ecofriendliness. Today, the transformer industry is witnessing the era of shifting from petroleum based mineral oils that are depleting, environmentally unfavorable, and proven dangerous to natural esters (vegetable oil based) that are renewable, environmentally friendly, and non-hazardous. The market and regulatory pressures to reduce liability risk exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 18 publications
1
46
0
1
Order By: Relevance
“…Rapeseed oil contains a high number of saturated fatty acids which make the oil oxidation stable and thus usable in long-term applications. As was mentioned above, the application of natural esters in transformers has several pros and cons [2,6,12]. The main advantage is their environmental compatibility, biodegradability and high flash (<200 • C) and fire points (<300 • C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapeseed oil contains a high number of saturated fatty acids which make the oil oxidation stable and thus usable in long-term applications. As was mentioned above, the application of natural esters in transformers has several pros and cons [2,6,12]. The main advantage is their environmental compatibility, biodegradability and high flash (<200 • C) and fire points (<300 • C).…”
Section: Discussionmentioning
confidence: 99%
“…From these overviews is visible that it is difficult to apply natural esters without further transformer adjustments. However, if all these features are already included in the machine design itself, the potential of natural esters can be fully utilized e.g., in areas of increased environmental protection [6], such as shopping centers, protected natural areas, natural parks, proximity to water sources, etc. The next possibility for using a natural ester is retrofilling mineral oil transformers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Mehta et al presents two reviews [22,23] in which many properties of both types of liquids are compared. As a result of this comparison, it is concluded that natural esters are acceptable for both new transformers and for retro filling existing units.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a huge development in the cleaning and the manufacturing processes of the oils and in the applied additives [9,18,[45][46][47]. Basically, two types of mineral oil based transformer oil are used: paraffinic-based and the naphthenic-based oils [48]. During the aging processes insoluble sludge has been produced in the case of paraffinic-based oils.…”
Section: Trends In Transformer Technologymentioning
confidence: 99%